Social structure of users of the city bus services in Maribor - Drozg, Vladimir (Journal for Geography, 2017)
This contribution shows the social structure of travellers on the city buses in Maribor. Data was obtained by watching the passengers who entered and exited buses at five selected bus stops through a period of five hours during the day. 27,082 passengers were evidenced. In addition to observations, we obtained data on social characteristics and travel habits of 532 persons who regularly use the bus transportation, and 77 persons who daily use a car. The following social groups which regular use the city buses are: retired female women, scholars and students and middle age employed men and women of middle class.
Keywords: social geography; social group; mobility; city bus service; Maribor